Prevalence, causes, and complications of cesarean delivery in Iran: A systematic review and meta-analysis - Rafiei, Mohammad (Int J Reprod Biomed, 2018)
BACKGROUND: Uncontrolled increase of C-section is one of the major problems in Iranian health system, such that C-section is the most common surgical procedure in the entire country’s hospitals in Obstetrics and Gynecology sections. A variety of complications also come along with cesarean. OBJECTIVE: The aim of this study was to evaluate the prevalence, causes, and complications of cesarean in Iran. MATERIALS AND METHODS: forty-one articles were considered with respect to certain criteria and were included in a systematic review to perform a meta-analysis study. The systematic review’s search was conducted on SID, Iranmedx, Magiran, Medlib, PubMed, and Science Direct databases published between1999-2016. The weight of each included study was calculated according to its sample size and the reported prevalence of binomial distribution. A random-effects model using R and STATA (Version 11.2) software was utilized for analyzing data RESULTS: The total number of the sample was 197514 pregnant women with a mean age of 26.72 yr. The prevalence of cesarean in Iran was estimated at 48%. The main reasons for the prevalence of cesarean in this study were mothers’ higher education, previous cesarean, and doctor recommendation. The most frequent complication in women undergoing cesarean was the muscular pain, and the most common fetal complications in newborns by caesarean delivery was transient tachypnea. CONCLUSION: The prevalence of C-section in Iran is much higher than what WHO recommends. It is essential, to decrease such a phenomenon, making the mothers aware of the risks of cesarean delivery, and establishing counselling sessions as well to eliminate the mothers’ fear of vaginal delivery.